Question
Work out \( (-6+4) \times(-5+9) \)
Ask by Rogers Logan. in Spain
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\(-8\)
Solution
Sure, let's work through the expression step by step:
\[
(-6 + 4) \times (-5 + 9)
\]
1. **First, solve the expressions inside the parentheses:**
- **Left Parentheses:**
\[
-6 + 4 = -2
\]
- **Right Parentheses:**
\[
-5 + 9 = 4
\]
2. **Now, multiply the results of the two parentheses:**
\[
-2 \times 4 = -8
\]
**Final Answer:** \(-8\)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
Let's break it down step by step! First, calculate the values inside the parentheses: \[ -6 + 4 = -2 \] \[ -5 + 9 = 4 \] Now, multiply the results of these two calculations: \[ (-2) \times (4) = -8 \] So, \( (-6+4) \times(-5+9) = -8 \).